Impact of BCR-ABL1 Transcript Type on Outcome in Chronic Myeloid Leukemia Patients Treated With Tyrosine Kinase Inhibitors: A Pairwise and Bayesian Network Meta-Analysis - Chen, Kangkang; Ruan, Yingying; Tian, Kewei; Xiong, Peisheng; Xia, Nan; Li, Jin; Huang, Wen; Cao, Feiyan; Chen, Qifeng (Frontiers in Oncology, 2022)
Purpose To evaluate the impact of BCR-ABL1 transcript type on outcome in chronic myeloid leukemia (CML) patients treated with tyrosine kinase inhibitors (TKIs). Methods PubMed, Embase and Cochrane library were systematically searched for relevant studies. Outcomes assessed were: major molecular response (MMR) at 6, 12, 18 and 60 months, deep molecular response (DMR) at 6, 12, 18 and 60 months, event-free survival (EFS), progression-free survival (PFS), overall survival (OS) and treatment-free remission (TFR). Odds ratios (ORs) and hazard ratios (HRs) were estimated and pooled using a random effect model. Results A total of 16 retrospective cohort studies involving 5,411 patients were included in this study. Compared with e13a2 transcripts, there was a statistically significant advantage for patients with e14a2 (alone or with co-expressed e13a2) in terms of MMR and DMR at 6, 12 and 18 months. This benefit was sustained up to 5 years for patients with e14a2 transcripts (OR 1.60, 1.23-2.07 and 2.21, 1.71-2.87, respectively), but not for patients with both transcripts. The expression of e14a2 also improved EFS (HR 0.71, 0.53-0.94) and OS (HR 0.76, 0.57-1.00) throughout treatment period. Importantly, having e14a2 transcripts were associated with a higher rate of TFR (OR 2.94, 1.70-5.08) in CML patients attempting TKI discontinuation. Bayesian network meta-analysis showed that e14a2 had the highest probability to be the most favorable transcript type for all outcomes, followed by both and e13a2. Conclusions The expression of e14a2 had a positive impact on MMR, DMR, EFS, OS and TFR. We suggest that in the future, the e14a2 transcript can be added to the list of prognostic factors to guide clinical decisions in treating CML.